TOXOPLASMOSIS IN PREGNANT WOMEN IN YEMEN: THE IMMUNE STATUS AND POTENTIAL RISK FACTORS - Alqaisi, Nashwa Abdullah Naji Saeed; AL-Mekhlafi, Abdulsalam M.; Al-Shamahy, Hassan A.; Al-Rukeimi, Abdullah AD; Foras, Kaima A.; Sheiban, Ali Abdulkarim (Universal Journal of Pharmaceutical Research, 2021)
Background and aims: Toxoplasmosis is caused as a result of intracellular protozoan organism, Toxoplasma gondii, and is a widespread disease. Toxoplasmosis can progress to a serious systemic disease (congenital form); once a mother becomes infected for the first time for the period of pregnancy, a transient haematopoietic parasite can appear with focal lesions produced within the placenta, thus infecting the fetus. Therefore, this cross-sectional study aimed at assessing the immune status of the pregnant woman towards toxoplasmosis, determining the prevalence of T. gondii in Amran city -Yemen, and identifying the potential risk factors that affect the pregnant woman towards toxoplasmosis. Material and methods: This study included 280 pregnant women who were admitted to maternity clinics at Amran General Hospital and Family Health Center in Amran City -Yemen during the period from December 2016 to June 2017. The questionnaire was used to obtain relevant demographic data and potential risk factors. Then, blood samples were collected from pregnant women and tested for identification of IgM and IgG antibodies against T. gondii using the ELISA technique. Results: The total positive rate for IgM antibodies was 3.6%, while for IgG was 27.9%. A high IgM rate equal to 5.3% was observed in the 31-35 age group, and a higher IgG rate (36.8%) was observed in the same age group. There were 69.3% of pregnant women susceptible to infection with toxoplasmosis, 2.9% recently infected, 27.1% protected, and 0.7% had secondary infection. The high rate of IgM positivity was observed in the second trimester of pregnancy (4.7%), while the lowest rate was in the third trimester of pregnancy (2%). A slight increase in the rate of IgG positivity was observed in the third trimester of pregnancy (32%). There was a significant association between contact with animals such as cats and infection with toxoplasmosis, where OR =5.4, CI =1.01-30.13, χ2 =4.59, p =0.04. While there was no significant association with the other studied factors. Conclusion: Yemen has less seropositivity than other Arab and African countries as a result of variation in risk factors. Data on T. gondii infection during pregnancy is scarce in numerous countries, in particular where there is a lack of political constancy such as Yemen. The risk factors identified included proximity to the cats and domistic animals, and increased maternal age. Toxoplasmosis in pregnancy in Yemen may be a really underestimated health problem. More research is needed. Peer Review History: Received 2 February 2021; Revised 7 March; Accepted 10 April; Available online 15 May 2021 Academic Editor: Dr. DANIYAN Oluwatoyin Michael , Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com Reviewer(s) detail: Rola Jadallah , Arab American University, Palestine, rola@aauj.edu Prof. Dr. Gorkem Dulger , Duzce University, Turkey, gorkemdulger@yandex.com